2015
DOI: 10.1080/10402004.2014.990593
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Behaviors of Carbon Fiber–Reinforced PEEK Sliding on Ion-Nitrided 2Cr13 Steel Lubricated with Tap Water

Abstract: Selecting the proper material and surface treatment methods for the elements is one of the essential problems when designing water hydraulic components due to the corrosiveness and poor lubricity of water. Experimental investigation was performed to study the tribological properties of ion nitrided 2Cr13, a kind of martensitic stainless steel, sliding on carbon fiber reinforced polyetheretherketone (CFRPEEK). The influence of factors such as sliding velocity, load, and lubrication condition were studied throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In order to satisfy the requirements of modern industry, like nonlubrication, high temperature, high load, corrosion, and so forth, PEEK was blended with other high‐performance polymers or compounded with fibers and other fillers to improve its mechanical, thermal, and tribological properties . Short carbon fiber (SCF) has been proved to be an effective reinforcement in improving the mechanical properties and wear resistance of PEEK …”
Section: Introductionmentioning
confidence: 99%
“…In order to satisfy the requirements of modern industry, like nonlubrication, high temperature, high load, corrosion, and so forth, PEEK was blended with other high‐performance polymers or compounded with fibers and other fillers to improve its mechanical, thermal, and tribological properties . Short carbon fiber (SCF) has been proved to be an effective reinforcement in improving the mechanical properties and wear resistance of PEEK …”
Section: Introductionmentioning
confidence: 99%
“…In order to meet the requirements of the modern industrial machinery, especially the requirements under high contact pressure and oil‐free lubrication conditions, many attempts have been tried to improve the tribological performance of PEEK by material scientists . Modification of PEEK with short carbon fiber (SCF) reinforcement and lubricant additives has been proved to be effective in improving the wear resistance of PEEK . It has been reported that the PEEK composites filled with 10–20 wt % SCFs have a relatively lower friction coefficient and specific wear rate than pure PEEK …”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Modification of PEEK with short carbon fiber (SCF) reinforcement and lubricant additives has been proved to be effective in improving the wear resistance of PEEK. 10,11 It has been reported that the PEEK composites filled with 10-20 wt % SCFs have a relatively lower friction coefficient and specific wear rate than pure PEEK. 12 Inclusion of organic and inorganic fillers improves the wear performance polymers effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3(b) shows that for the two lubricants, the friction coefficients present an increasing trend with sliding speeds at the applied load of 125 N. The evolution of friction coefficients for the water–silica mixture lubrication improves sharply when sliding speed is over 15 mm/s. The friction coefficient for the water–silica mixture lubrication is enhanced by 31.6 per cent when the sliding speed increases from 15 to 35 mm/s, which is the result of significant effect of the SiO 2 on increasing the boundary lubricating ability of water (Shukla et al , 2016; Tang et al , 2015) and lots of oxide layers spall away due to the increasing hot pressure caused by SiO 2 particles with the high sliding speed. Figure 3(c) shows that with the same sliding distance (45 m), the mass wear rates increase with the increasing sliding loads, which is caused by the increasing ploughing effects of abrasives and SiO 2 particles.…”
Section: Resultsmentioning
confidence: 99%
“…Lubrication plays a very important role during the sliding process, in which the water acts as both a lubricant and a coolant (Wahlström, 2014; Engelhardt et al , 2017). For the low viscosity, corrosive properties and poor boundary lubrication properties, the tribological behavior of alloy steel with water lubrication is different with other lubrication and the dry sliding (Tang et al , 2015; Wang et al , 2014). The water film over the sliding surface contributes to decrease the friction coefficient and increase the abrasion resistance (Wu et al , 2016).…”
Section: Introductionmentioning
confidence: 99%